1999
DOI: 10.1016/s0927-7757(99)00120-x
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants role on the deformation of colliding small bubbles

Abstract: The mutual approach of two bubbles and the rate of thinning and the deformation of the partially mobile thin liquid film intervening between them is studied. The material properties of the interfaces (surface viscosity, Gibbs elasticity, surface and/or bulk diffusivity) are taken into account. In the normal stress balance at the fluid interfaces we include the contribution of the intermolecular forces. To obtain the liquid velocity and pressure distribution the lubrication approximation is used. From the norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 23 publications
(60 reference statements)
1
27
0
Order By: Relevance
“…The reality could be more complex-for example, the surfaces could be partially mobile and, in this case, more complex boundary conditions at the bubble surface are required. [11][12][13]63 To find a general solution for this theoretical problem is an extremely difficult task which has not been solved so far. However, theoretical models for some specific cases (diffusion or barrier control of surfactant adsorption), [82][83][84] as well as some preliminary estimates accounting for the effects of surface elasticity 85 have shown that the power-law index m could vary in wide range, including values which are significantly lower than 1/2.…”
Section: 2346mentioning
confidence: 99%
See 1 more Smart Citation
“…The reality could be more complex-for example, the surfaces could be partially mobile and, in this case, more complex boundary conditions at the bubble surface are required. [11][12][13]63 To find a general solution for this theoretical problem is an extremely difficult task which has not been solved so far. However, theoretical models for some specific cases (diffusion or barrier control of surfactant adsorption), [82][83][84] as well as some preliminary estimates accounting for the effects of surface elasticity 85 have shown that the power-law index m could vary in wide range, including values which are significantly lower than 1/2.…”
Section: 2346mentioning
confidence: 99%
“…), because the foam behaviour is governed by relatively well understood interplay of capillary effects and viscous friction in the foam films, formed between neighbouring bubbles. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18] In addition, the relatively large bubble size allows direct optical observation of the dynamics of individual bubbles in flowing foams. [18][19][20][21] All these circumstances provide unique possibility for detailed theoretical modelling and experimental studies of foams at a microstructural level, which is impossible for the other systems of interest.…”
Section: Introductionmentioning
confidence: 99%
“…From this pressure balance one can derive the following expression for the initial film thickness, , where μ is dynamic viscosity of continuous phase, σ is interfacial tension, and R N is radius of curvature of the bubble surface in the contact zone, just before the foam film formation [12,15]. As in Ref.…”
Section: Figmentioning
confidence: 99%
“…Manor, Lavrenteva & Nir (2008) extended LeVan's results to account for variable surface viscosities. Valkovska, Danov & Ivanov (1999) studied how the deformation of bubbles, a related physical model, is affected by surface viscosity and Marangoni stress during collisions. More recently, the effect of surface viscosity on the dynamics of a spherical droplet in Poiseuille flow has been studied.…”
Section: Introductionmentioning
confidence: 99%